POVERTY REDUCTION THROUGH UPTPK (THE INTEGRATED SERVICE UNIT OF POVERTY ALLEVIATION) IN SRAGEN REGENCY CENTRAL JAVA PROVINCE - Titik Djumiarti; Ari Subowo (Journal of Public Administration and Local Governance, 2018)
The existence of UPTPK in Sragen Regency is an effort of the regional government in Sragen Regency to tackle the poverty with a systematic and integrated concept. The success of Sragen Regency in the establishment of UPTPK to the poverty tackling program can encourage the Social Ministry to give an appreciation through a program named GEMPITA (Regency/City Concerned Community Movement). The purpose of this writing is to explain the leadership of Agus Fatchur Rahman in maintaining the poverty through UPTPK (The Integrated Service Unit of Poverty Tackling) in Sragen Regency. democratic leadership and gives his staff the freedom to develop in providing services to the society. Through UPTPK, Agus Fatchur Rahman seeks to provide and improve the welfare of the society through special services in the education, health, and social and economic. The establishment of UPTPK is a step by Regent Agus Fatchur Rahman to articulate the needs and interests of the poor society to improve their welfare. Viewed from each dashboard, the leader of Sragen Regency needs to make efforts to encourage better management of UPTPK, including increasing accountability through reporting on the performance of UPTPK in print so that reporting is not only electronic reporting but also print reporting to facilitate the society who come to the office obtain the performance information. Keywords: Poverty Reduction, Leadership, Integrated Service